The Meaning of Leadership for Leaders of Private Universities in Indonesia - Yosua, Immanuel; Murniati, Juliana; Panggabean, Hana (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
Leading a university is generally more complex than a business organization, as the situation requires the presence of a leader who not only meets the criteria but is also willing to lead, a very rarely found combination in universities. Interestingly, although it is not easy to find academics with such qualities, these people still exist because they see the importance of leading for the survival of the organization. Therefore, it becomes interesting to understand how they ascribe meaning to their leadership amid the difficulties they must deal with. This study was conducted using in-depth interviews with 13 academic leaders to ascertain how they ascribe meaning to their leadership. The results of the interviews were then analyzed using the Atlas.ti 8 software. Four interpretive themes emerged from the interviews: (1) the many faces of university leaders; (2) community leadership style; (3) knowledge development and non-profit oriented leadership mission; and (4) corporate leadership.